A novel graphene-wrapped corals-like NiSe2 for ultrahigh-capacity potassium ion storage. (May 2020) - Chu, Jianhua; Yu, Qiyao; Han, Kun; Xing, Lidong; Bao, Yanping; Wang, Wei (Alex)
Abstract: Room-temperature potassium-ion batteries (KIBs) are attracting increasing attention for grid-scale energy storage owing to abundant raw potassium resources and competitive energy density. However, exploring high-performance anode materials remains challenging, and one of the major problems is the sluggish movement of heavy and large K + ions between electrodes. This study reports a designed corals-like NiSe2 attached to graphene matrix (NSG) via a colloidal method and subsequent coating procedure, which is firstly applied as an anode material for KIBs. Benefitting from the enhanced electronic conductivity and volume expansion mitigation, the NSG composite exhibits excellent potassium storage performance, achieving unprecedented reversible specific capacity as high as 522 mAh g −1  at 50 mA g −1 over 50 cycles, superior rate performance (272 mAh g −1  at 1000 mA g −1 ) and long-term life (259 mAh g −1 over 1200 cycles at 1000 mA g −1 ). Besides, partial capacity contribution derived from pseudocapacitive charge storage behaviors of the redox reactions upon cycling with fast K + diffusion kinetics is also studied. This work provides a reasonable design of selenides and carbon-based composite anodes with ultrahigh capacity and long lifespan for advanced KIBs. Graphical abstract: The table of contents entry. A corals-like NiSe 2 attached to graphene matrix (NSG) composite is synthesized via a colloidal method and subsequent coating procedure and firstly applied as an anode material for potassium-ion batteries (KIBs). Benefitting from the enhanced electronic conductivity and volume expansion mitigation, the NSG composite exhibits unprecedented reversible specific capacity, superior rate performance and excellent cycling stability. Image 1 Highlights: A well-designed corals-like NiSe2 is successfully synthesized via a colloidal method. The NiSe2 embedded on graphene matrix (NSG) composite possesses the enhanced electronic conductivity and volume expansion mitigation. The NSG composite is firstly applied as an anode material for potassium-ion batteries. The NSG composite exhibits ultrahigh reversible specific capacity and superior rate performance.